Pendidkan Seksual Di LP Maarif Untuk Mengurangi Permohonan Dispensasi Nikah Sebagai Ihtiar Membangun Peradaban Manusia - Fajrin, Ahmad Hanif; Fahmi, Moh. Farih; Ainun, M. Thoha (CV. Gerasi Insan Nusantara, 2023)
This article tries to examine and discuss the role of the Nahdlatul Ulama in minimizing requests for dispensation from marriage that occurred in several areas in East Java, one of which is in Blitar. This request for a marriage dispensation is one of the challenges because it can damage the nation's civilization which has noble cultural values. There are several things discussed in this article which include (1) the impact of the Marriage Dispensation on national civilization; (2) The role of LP Ma'arif NU Blitar in minimizing the factors causing the dispensation of marriage; (3) what is the multiperspective perspective of marriage dispensation for national civilization. The results of this study are that the application for a marriage dispensation is not in accordance with a good solution because it can have an impact on society, the economy and the Islamic religion. To minimize this, Nahdlatul Ulama (NU) needs the important role of the LP Maarif institution as an institution assigned to oversee formal educational institutions under NU whose citizens are dominant in East Java, especially in Blitar Raya